Influence of Probiotics Supplementation on Performance of Broilers - Bharathidhasan, A. (International Journal For Research In Agricultural And Food Science, 2018)
An experiment was conducted to study the effect of probiotics supplementation on performance of broilers in terms of body weight, feed intake and feed efficiency. Forty two Vencobb broiler straight run chicks were wing banded, weighed individually and distributed randomly in to two experimental diets with and without supplementation of probiotics. The probiotic contained Lactobacillus species. The birds were housed in deep litter pens and reared from day one to six weeks following uniform standard managemental practices. Feed intake was recorded daily, body weight was taken at weekly intervals and weight gain and feed efficiency worked out for 0-6 weeks. The weight gain was significantly (p<0.05) increased by 5.8 % in probiotic supplemented groups than without supplemented group. The feed intake was not affected by probiotic supplementation. However it was numerically decreased in probiotic supplemented group when compared to control. Mean feed efficiency was significantly (p<0.05) better in probiotic supplemented group than control. The improvement in feed efficiency was 8.8% in probiotic supplemented group when compared to control. It was concluded that the probiotic supplementation was significantly increased weight gain and feed efficiency in broilers.